2016
DOI: 10.1139/tcsme-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

DRY SLIDING WEAR BEHAVIOR OPTIMIZATION OF STIR CAST LM6/ZrO2 COMPOSITES BY RESPONSE SURFACE METHODOLOGY ANALYSIS

Abstract: LM6 was reinforced with various percentages of ZrO2 particles by using stir casting method. The prepared samples were subjected to tensile and wear test at variable loads by using a pin-on-disc wear tester. The curve fitting technique was used to develop the respective linear, logarithmic, polynomial, power law equations. The wear worn surface and surface roughness of the specimen were studied. Response Surface Methodology (RSM) was used to minimize the number of experimental conditions and develop the mathema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…It is observed that the hardness values of the material is directly proportional to the presence of ZrO 2 with the increase in ZrO 2 , the hardness increases. Similar trends have been observed by many other researchers [5,20]. , it can be seen that, ZrO 2 content increases, the ductility of the composite material increases monotonically by significant amounts.…”
Section: Effect Of Hardnesssupporting
confidence: 90%
See 2 more Smart Citations
“…It is observed that the hardness values of the material is directly proportional to the presence of ZrO 2 with the increase in ZrO 2 , the hardness increases. Similar trends have been observed by many other researchers [5,20]. , it can be seen that, ZrO 2 content increases, the ductility of the composite material increases monotonically by significant amounts.…”
Section: Effect Of Hardnesssupporting
confidence: 90%
“…Metal Matrix Composites (MMCs) have emerged as an important class of materials for structural, wear, thermal, transportation and electrical applications because it offers high strength to weight ratio, high stiffness and good wear resistance [3][4]. The aluminum based metal matrix composites are excellent novel materials for applications in aerospace, automotive and transportation industries [5][6]. The fabrication methods of the aluminum based composites can be categorized into three processes: solid-state methods, semisolid state methods and liquid state method [5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the increase in the ZrO 2 reinforcement ratio in the composite structure led to gradual decrease in the wear losses. Similar results are reported in the studies in the literature (Ramachandra et al, 2015;Karthikeyan and Jinu, 2015a;Karthikeyan and Jinu, 2016;Madhusudhan et al, 2016;Pandiyarajan et al, 2017;Veeresh Kumar et al, 2019). In another study in the literature, it was stated that the oxide formed at the matrix-reinforcing interface plays an important role in reducing both the friction coefficient and the amount of wear (Karthikeyan and Jinu, 2015b).…”
Section: Effect Of Zro 2 Ratio On the Wearsupporting
confidence: 81%
“…The literature review showed that MMCs play a vital role in replacing metals, due to their advanced mechanical and metallurgical properties. A lot of researchers have concentrated on developing new composites such as Al 6061, LM14, LM25 reinforced with various elements such as TiB 2 , SiC, TiC, ZrB 2 , AIN, Si 3 N 4 , Al 2 O 3 and their wear properties were analyzed in earlier studies [4][5][6][7][8][9][10][11][12]. No papers have been found to analyze the effect of MgO on the LM14 base material while subjected to finite element analysis.…”
Section: Introductionmentioning
confidence: 99%